Age at menarche and prevention of hypertension through lifestyle in young Chinese adult women: result from project ELEFANT - Liqiong Guo; Cheng Peng; Hui Xu; Ander Wilson; Peng-hui Li; Hao Wang; Hongbin Liu; Lilin Shen; Xi Chen; Xiuying Qi; Nai-jun Tang; Timothy M. Barrow; et al. (BMC, 2018)
Abstract Background Early and late age at menarche are associated with risk of hypertension, but little is known whether modifiable lifestyle can reduce this risk. Methods Our study leverages 60,135 healthy young Chinese women from the Environmental and LifEstyle FActors iN metabolic health throughout life-course Trajectories (ELEFANT) study. Menarche age and lifestyle factors were assessed by self-reported questionnaires and hypertension was diagnosed by physicians. We estimated the odds ratios (ORs) of hypertension associated with menarche age using multivariable logistic regression. We further investigated whether modifiable lifestyles (body mass index, BMI; psychological stress; passive smoking; and imbalanced diet) increased risk in joint analyses. Results The association between age at menarche and hypertension was U-shaped, with age ≤ 12 at menarche giving the highest OR (1.46, 95% confidence interval [CI], 1.27-1.69) and ≥ 16 the second highest (OR = 1.36, 95% CI = 1.15-1.62). Simultaneous analysis of lifestyle risk factors and age of menarche showed that having one or more modifiable risk factors increased the menarche age-hypertension association. The risk of hypertension among participants with menarche age ≤ 12 decreased from OR 13.21 (95% CI = 5.17-29.36) with four high-risk lifestyle factors to 12.36 (95% CI = 9.51-16.05) with three high-risk factors, 5.24 (95% CI = 4.11-6.69) with two, and 2.76 (95% CI = 2.09-3.60) with one, in comparison to individuals with no high-risk lifestyle factors and menarche age 14. Conclusions Our results suggest that modification of lifestyle, including maintenance of normal weight and a balanced diet, are associated with substantially reduce the risk of hypertension in high-risk individuals. Plain English summary Early and late age at menarche are risk factors for the development of hypertension in Western populations, and there is limited evidence that this is also true of Chinese populations. Targeted prevention of hypertension in vulnerable populations would be highly beneficial in efforts to reduce the incidence of cardiovascular disease, but it is not currently known whether lifestyle intervention could reduce hypertension risk. In this study, we analysed the risk of hypertension by age at menarche and four modifiable lifestyle factors (BMI, diet, psychological stress, and smoking tobacco) in a cohort of 60,135 young adult Chinese women (mean age 29). We identified that early and late age at menarche are associated with increased risk of hypertension in young Chinese women. There was joint effects between age at menarche and lifestyles on hypertension only participants with age at menarche ≤12 and being overweight or obese. Modification of lifestyle, including maintenance of normal weight and a balanced diet, can substantially reduce the risk of hypertension in high-risk individuals. In conclusion, our study has revealed that early and late menarche age are associated with the development of hypertension in young Chinese women, and that this risk is modified by healthy lifestyle traits.